Pharmacotherapeutic Strategies in High-Risk Pregnancy: Balancing Maternal and Foetal Safety - Saroha, Geeta; Das, Rina; Mehta, Dinesh Kumar (Scripta Medica, 2026)
Pharmacotherapy in high-risk pregnancies necessitates customised, evidence-based strategies to provide optimal results for women and their infants. A keen awareness that physiological changes during pregnancy can affect medication pharmacokinetics necessitates careful consideration of dose and therapeutic selection to reduce teratogenic risk without compromising treatment efficacy. Likewise, non-obstetric problems such as hypertension in pregnancy, gestational diabetes, auto-immune disorders and infections necessitate immediate medical intervention according to safety classifications and evolving labelling systems. Multidisciplinary care involving obstetricians, pharmacists, subspecialists and mental health professionals is crucial for managing the intricate relationships between maternal comorbidities and foetal development. Moreover, emerging domains including pharmacogenomics, placental-drug-delivery and diversity in clinical trials are further transforming the future of perinatal pharmacotherapy. This article aimed to examine the role of pharmacotherapy in high-risk pregnancies, emphasising the contemporary paradigm of safe drug use, collaboration within a multidisciplinary framework and prospective advancements to optimise maternal and foetal health outcomes. The personalised, evidence-based pharmacotherapeutic approach that improves high-risk pregnancy outcomes is based on body modifications, safe medication use, multidisciplinary approaches and advances in pharmacogenomics and placenta-targeted therapies.
Keywords: High-risk pregnancy; Pharmacokinetics; Therapeutics; Obstetricians; Comorbidity